SEX DIFFERENCES IN THE TRAUMA-RELATED SYMPTOMS – A PILOT STUDY - Jerotić, Stefan; Marić Bojović, Nadja (Medicinski podmladak, 2016)
Introduction: During the year 2014, a part of the population from Serbia was exposed to floods. After natural disasters and other types of extreme trauma, some people will be more affected by trauma than others. How women and men differ, in the symptoms that can manifest after the exposure to extreme trauma, is still an open question. Aim: To evaluate if there are differences in the severity of trauma-related symptom clusters between the sexes (re-experiencing, avoidance, negative cognitions and mood, and arousal; according to DSM V) and in expiriencing negative emotional states (depression, anxiety, stress). Material and methods: Forty healthy volunteers from Obrenovac (25 women and 15 men) were administered with three instruments: The Life Events Checklist − LEC-5, PTSD checklist for DSM V – PCL-5 and Depression Anxiety Stress Scale − DASS. Results: The majority of subjects reported floods as the major lifetime trauma (72.5%). Despite the relatively low level of the post-traumatic symptom intensity (5.02 ±4.99), women exhibited significantly higher total post-traumatic symptom severity scores in comparison to men (p